Cultural Semantics of Evaluation: A Linguocultural Study of Good/Bad and Yaxshi/Yomon in English and Uzbek - Ergasheva Dilafruz Abdusalomovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
While culture is considered the most essential indicator and distinctive feature of both the individual and society, then language, as the primary tool of communication in human life and social interaction, occupies a crucial and irreplaceable place. In other words, language and culture are inseparable; they represent two interdependent parts reflecting one another. But what is culture, essentially? "Culture is an intangible force that organizes the world and incorporates it into a system of human values."1 Since culture organizes the world, it inevitably structures language as well— playing a role in its formation and manifesting itself through it. The lifestyle and consciousness of any society, as well as the language it employs, are intimately connected to its culture. Indeed, the culture of a people is directly reflected in their language and vocabulary. For example, the Uzbek word ―маҳалла‖ does not have an exact equivalent in English. Although it is often translated as ―neighbourhood,‖ the English term fails to fully convey the socio-cultural meaning embedded in ―маҳалла‖ within Uzbek culture. This is primarily due to the absence of the маҳалла institution and the related social concept in English society.